Policies To Overcome Unemployment In Indonesia And Korea During The Covid-19 Pandemic - Herijanto Bekti (SEAN Institute, 2023)
This paper will discuss the policies that have been put in place related to the labor market in Indonesia and Korea, especially during the Covid-19 pandemic. Many problems occurred during the Covid-19 pandemic, such as the increasing number of unemployed, reducing working hours. The research design used is descriptive qualitative research. The author uses a literature study and is reviewed using the SLR (Systematic Literature Review). Literature study by making summaries sourced from secondary data such as Scopus indexed articles, books, and other documents related to research. Each country has made policies to overcome the unemployment problem that occurred during the Covid-19 pandemic, workers are given assistance and training to be able to help fulfill daily life and create opportunities to get through the existing crisis. However, several policies that have been made have not been able to completely solve the problem, especially related to the differences in the problems faced between male workers and female workers, should be done with a different approach.